An Approach in Coloring Semi-regular Tilings on the Hyperbolic Plane - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2005)
A coloring of a semi-regular tiling is perfect if every symmetry of the tiling permutes the colors of the tiling. In this paper, an approach to the construction of perfect colorings of semi-regular tilings on the hyperbolic plane is presented.